Assessment of the Ministry's Unified Exams in West Bank Governorates from the Points of View of Administrators and Technicians - Mohammad Abdul-Kareem Mahmoud AL-qasim (My University, 2016)
The study aimed at assessing the Ministry's unified exams in the governorates of the West Bank from the perspectives of administrators and technicians in accordance with variables like sex, qualification, experience, career, and the directorate of education. The population of the specimen of the study consisted of directors of education, their administrative and technical deputies, heads of supervision departments, as well as supervisors of school subjects targeted by these tests. The total number of the targeted group is (387), about (340) of these responded. The research adopted the descriptive approach that matches the nature of the study. To achieve the aims of the study, the researcher set up a questionnaire that consisted of (74) paragraphs with six domains for the assessment of the Ministry's unified exams. These include: the policy and aims of the exams along with their rules, technical aspects of exams, stages of exams implimentation, the teachers, the students, as well as the curriculum. The research confirmed the validity and consistency of the questionnaire. The results of the study showed that assessing the Ministry's unified exams from the perspectives of education administrators and technicians were average. The study also shows differences in the assessment of the Ministry's unified exams in the perspectives of education administrators and technicians due to variables like sex, career and the directorate of education. The difference was in favour of males in terms of sex, for education administrators in terms of career and in favour of the directorate of education (Qalqilia, Qabatya, Ramallah, Salfeet, AL-Quds) in accordance with the directorate of education variable. However, no differences are found due to variables like professional qualification, and administrative and supervision experience. In accordance with these results, the study recommends that the ministry of education should show more interest to the recommendations and notes collected by professionals who work in the field of schooling, particularly supervisors who follow up the school subjects targeted by the ministry's unified exams. This feedback should be considered to comprehensively develop and improve these exams. Key words: Assessment, Unified Exams, Administrators, Technicians.

هدفت هذه الدراسة التعرف إلى تقييم الاختبارات الوزارية الموحدة في محافظات الضفة الغربية من وجهات نظر الإداريين والفنيين، وفقاً للمتغيرات الآتية: (الجنس، المؤهل العلمي، الخبرة الإدارية والإشرافية، الوظيفة، المديرية). وتكوّن مجتمع الدراسة من جميع أفراد المجتمع المؤلف من مديري التربية والتعليم، ونوابهم الإداريين والفنيين، ورؤساء أقسام الإشراف التربوي، والمشرفين التربويين الذين يشرفون على المباحث التي تستهدفها هذه الاختبارات، البالغ عددهم (387) إدارياً وفنياً، أما العينة فقد تكونت من (340) إدارياً وفنياً. واستخدم الباحث المنهج الوصفي لمناسبته وطبيعة الدراسة، ولتحقيق أهداف الدراسة أعدّ الباحث استبانة مكونة من (74) فقرة، وشملت ستة مجالات لتقييم الاختبارات الوزارية الموحدة وهي: سياسة وأهداف الاختبارات وتشريعاتها، الجوانب الفنية للاختبارات، مراحل تطبيق الاختبارات، المعلم، الطالب، المنهاج، حيث تأكد الباحث من صدق الأداة وثباتها. وقد أظهرت نتائج الدراسة أن تقييم الاختبارات الوزارية الموحدة من وجهات نظر الإداريين والفنيين جاءت بدرجة متوسطة، كما أظهرت وجود فروق في تقييم الاختبارات الوزارية الموحدة من وجهات نظر الإداريين والفنيين تعزى لمتغيرات (الجنس، والوظيفة، والمديرية)، حيث كانت الفروق لصالح الذكور تبعاً لمتغير الجنس، وللإداريين تبعاً لمتغير الوظيفة، ولمديريات التربية والتعليم (قلقيلية، قباطية، رام الله، سلفيت، القدس) تبعاً لمتغير المديرية، كما أظهرت نتائج الدراسة عدم وجود فروق تعزى لمتغيرات (المؤهل العلمي، والخبرة الإدارية والإشرافية). وفي ضوء هذه النتائج أوصت الدراسة بضرورة اهتمام وزارة التربية والتعليم العالي بملاحظات العاملين في الميدان التربوي وتوصياتهم، وخصوصاً المشرفين التربويين الذين يشرفون على المباحث التي تستهدفها الاختبارات الوزارية الموحدة، والأخذ بها في تطوير هذه الاختبارات وتجويدها من جميع الجوانب. الكلمات المفتاحية: التقييم، الاختبارات الوزارية الموحدة، الإداريين، الفنيين.
تقييم الاختبارات الوزارية الموحدة في محافظات الضفة الغربية من وجهات نظر الإداريين والفنيين